TRANSFUSI DARAH DAN EUTHANASIA - Abdul Wahab Syakhrani; Rahmilasari, Raisa Nabilla, Nor Hidayati, Tri Octa Aulia Nabella (Jurnal Kesehatan, 2024)
The word blood transfusion is a translation of "bloodtransfusion", namely from English. Then an Arabic doctor translated it as "blood transfer caused by a medical need". Then it was interpreted as "moving and then pouring blood" by Dr. Ahmad Sofyan. Then he formulated the definition of blood transfusion with the meaning, "transferring blood means putting blood through a blood vessel to another person who is being helped." The term euthanasia comes from the Greek, namely "eu" and "thanatos". The word "eu" means good, without suffering and thanatos means death, therefore when we say euthanasia the real meaning is not to cause death, but to reduce or alleviate the suffering of people who are facing death.